(untitled) (Journal of Innovative Research, 2025)
This research study analyzes the formatting and language used in notifications and orders issued by the Government of Punjab in Pakistan. It examines how these legal documents are arranged and structured, the terminology utilized, and how these impact formal communications and public access to information. A range of notifications and orders were inspected, such as those relating to public health initiatives and law enforcement activities. The evaluation reveals that a consistent structure is applied with distinct sections like headings, introductions, primary content sections, and conclusions. Appropriate legal citations are incorporated to affirm precision and standing. This formal register highlights the necessity of adhering to pertinent rules and regulations. However, a persisting challenge remains that the complex legal terminology employed in these documents renders the legislation obscure for most citizens. Only individuals with specialized training can fully comprehend the communications. The paper proposes adopting innovative methods for alternative government divisions to develop informational content employing straightforward terminology comprehensible to all. It also recommends improving digital access to these legal notices and adapting outreach methods for varied audiences. The overarching goal is to strike the equilibrium between preserving legal accuracy while also guaranteeing the general public can easily grasp messages from governing bodies, which is essential for cultivating trust and good governance.